Adolescent idiopathic scoliosis: The mechanobiology of differential growth. Issue 4 (24th July 2020) - Smit, Theodoor H.
Abstract: Adolescent idiopathic scoliosis (AIS) has been linked to neurological, genetic, hormonal, microbial, and environmental cues. Physically, however, AIS is a structural deformation, hence an adequate theory of etiology must provide an explanation for the forces involved. Earlier, we proposed differential growth as a possible mechanism for the slow, three‐dimensional deformations observed in AIS. In the current perspective paper, the underlying mechanobiology of cells and tissues is explored. The musculoskeletal system is presented as a tensegrity‐like structure, in which the skeletal compressive elements are stabilized by tensile muscles, ligaments, and fasciae. The upright posture of the human spine requires minimal muscular energy, resulting in less compression, and stability than in quadrupeds. Following Hueter‐Volkmann Law, less compression allows for faster growth of vertebrae and intervertebral discs. The substantially larger intervertebral disc height observed in AIS patients suggests high intradiscal pressure, a condition favorable for notochordal cells; this promotes the production of proteoglycans and thereby osmotic pressure. Intradiscal pressure overstrains annulus fibrosus and longitudinal ligaments, which are then no longer able to remodel and grow, and consequently induce differential growth. Intradiscal pressure thus is proposed as the driver of AIS and may therefore be a promising target for prevention and treatment. Abstract : Differential growth has been suggested as a physical mechanism for spinal deformations in Adolescent Idiopathic Scoliosis. Here, the underlying mechanobiological mechanisms are explored and it appears that high intradiscal pressure may be responsible for overstraining the annulus fibrosus and longitudinal ligaments, thereby inducing differential growth.